The actin modulator hMENA regulates GAS6‐AXL axis and pro‐tumor cancer/stromal cell cooperation. (10th September 2020) - Melchionna, Roberta; Spada, Sheila; Di Modugno, Francesca; D'Andrea, Daniel; Di Carlo, Anna; Panetta, Mariangela; Mileo, Anna Maria; Sperduti, Isabella; Antoniani, Barbara; Gallo, Enzo; Lawlor, Rita T; Piemonti, Lorenzo; et al.
Abstract: The dynamic interplay between cancer cells and cancer‐associated fibroblasts (CAFs) is regulated by multiple signaling pathways, which can lead to cancer progression and therapy resistance. We have previously demonstrated that hMENA, a member of the actin regulatory protein of Ena/VASP family, and its tissue‐specific isoforms influence a number of intracellular signaling pathways related to cancer progression. Here, we report a novel function of hMENA/hMENAΔv6 isoforms in tumor‐promoting CAFs and in the modulation of pro‐tumoral cancer cell/CAF crosstalk via GAS6/AXL axis regulation. LC‐MS/MS proteomic analysis reveals that CAFs that overexpress hMENAΔv6 secrete the AXL ligand GAS6, favoring the invasiveness of AXL‐expressing pancreatic ductal adenocarcinoma (PDAC) and non‐small cell lung cancer (NSCLC) cells. Reciprocally, hMENA/hMENAΔv6 regulates AXL expression in tumor cells, thus sustaining GAS6‐AXL axis, reported as crucial in EMT, immune evasion, and drug resistance. Clinically, we found that a high hMENA/GAS6/AXL gene expression signature is associated with a poor prognosis in PDAC and NSCLC. We propose that hMENA contributes to cancer progression through paracrine tumor–stroma crosstalk, with far‐reaching prognostic and therapeutic implications for NSCLC and PDAC. Synopsis: This study reveals that inhibition of hMENA/hMENADv6 expression reduces pro‐tumor CAF‐cancer cell crosstalk and inhibits cancer cell invasiveness. CAFs with a pro‐tumor activated state express higher levels of hMENA/hMENADv6 compared to normal fibroblasts. CAFs over‐expressing hMENADv6 secrete GAS6 and favor the invasiveness of AXL‐ expressing PDAC and NSCLC cells. Reciprocally in tumor cells hMENA/hMENADv6 regulate AXL expression, and sustain GAS6‐AXL paracrine axis. A high hMENA/GAS6/AXL gene expression signature identifies PDAC and NSCLC patients with a poor prognosis. Abstract : This study reveals that inhibition of hMENA/hMENADv6 expression reduces pro‐tumor CAF‐cancer cell crosstalk and inhibits cancer cell invasiveness.